Vitamin D sebagai Pencegahan Penyakit Degeneratif hingga Keganasan: Tinjauan Pustaka - Riskita Fiannisa (Medula, 2019)
Vitamin D is a vitamin that is often forgotten but has many benefits that are very beneficial for our body. Vitamin D or alsocalled a sunshine vitamin is obtained from inside the body and outside the body. The source from the body that vitamin Dcomes from 7-dehydroxylase which is in the epidermis and dermis layer which will transform into an active form of vitamin Dproduced by UVB radiation. Vitamin D which is synthesized with the help of sunlight is the main supply of vitamin D and thatlasts longer than vitamin D which comes from food sources. Factors causing vitamin D deficiency such as sunscreen, skinpigmentation, dress code, elderly, season and temperature of the region, medical conditions such as liver disorders, chronickidney disorders, and use of anticonvulsants, fat malabsorption, and obesity can use their use of vitamin D content inside thebody. There are many diseases related to vitamin D in the body, such as osteoporosis, rickets, fractures, weakness, cancer,diabetes, fat malabsorption, chronic kidney disorders, liver disorders and obesity. This research discusses the importance ofvitamin D for the body and can also help vitamin D in preventing various diseases. The benefits of vitamin D for the body canprevent diabetes, prevent cancer, and prevent cardiovascular disease, osteoporosis, and rickets.